Les Amputations Majeures Des Membres A L’hopital General De Reference Nationale De N’djamena, Tchad - Ouchemi, Choua; Abdoul, Touré; Dionadji, Mbainguinam; Chaib, Mahamat Albichari Ahmat; Okim, Ahmat Malgnan; Maide, Moussa Kalli (European Scientific Journal, ESJ, 2016)
The aim of this study was to describ major limb amputations in a tertiary teaching hospital in N’Djaména, Chad. Patients and Method We realized a both retrospective and prospective study from 01/08/2013 to 31/07/2015 in the General Surgery ward and Orthopedics and Traumatology ward of the National Reference General Hospital of N’Djamena, Chad. Data were collected from patient records, operating theater records and equipment center. Studied parameters: age, sex, indication and level of amputation, length of hospital stay, prosthetic devices and mortality. Results The study population included 155 patients divided into 118 men (70.1%) and 37 women (29.9%), a sex ratio of 2.3. The average age was 43.1 years. Severe limb injuries by road traffic crushes were the first major amputation indication in 74 cases (47.6%), followed by complications of diabetic ulcers in 33 cases (21.4%) and arterial occlusive disease in 21 cases (13.6%). The pelvic and thoracic limbs were affected respectively in 130 cases (84.9%) and 25 cases (16.1%). The levels of amputations were: the leg in 78 cases (50.3%), the thigh in 50 cases (32.3%) and the forearm in 9 cases (5.8%). The average hospital stay was 16 days. We noted wound suppuration in 28.4% of cases and psychiatric events in 4.6%. Mortality was 15.6%. Only 35 patients (22.6%) received a prosthetic device after amputation. Conclusion: road traffic trauma with irreversible vascular damage is the leading indication of major limb amputations in our setting. Complications of diabetic foot are increasing indication. Mostly, traditional bonesetters practiced on the patients before reaching to hospital care. The amputees face great prosthetic difficulties. Major limb amputations are preventable by education, early presentation and management of common indications.